Strategi Manajemen Adaptif dalam Model Kerja Hybrid pada Jasa Online Delivery di Mandailing Natal - Mufti Fahrizal Harahap (LPPM Universitas Bina Sarana Informatika, 2025)
Changes in work patterns due to digitalization and the pandemic have encouraged service companies, including online delivery services, to adopt a hybrid work model. In Mandailing Natal, this model presents challenges such as limited infrastructure, team coordination, and dynamic market demand. Therefore, adaptive management strategies are required to maintain optimal performance. This study employs a descriptive qualitative approach using in-depth interviews with managers, couriers, and customers from three online delivery service companies in Mandailing Natal. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that adaptive management strategies in the hybrid work model are implemented through three main steps: (1) adjusting the work structure between online and offline, (2) providing flexibility in scheduling and courier work rotation, and (3) utilizing digital technology for monitoring and communication. In addition, local factors such as geographical conditions and consumer habits are key considerations in adapting these strategies. Adaptive management strategies have been proven to improve operational effectiveness and customer satisfaction in online delivery services in Mandailing Natal. The adaptively managed hybrid work model is not only a solution to changing business environments but can also serve as a sustainable work pattern for digital-based services in regions with infrastructural limitations.